SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN VOLUME PRODUKSI ROTI MENGGUNAKAN METODE SIMPLEKS PADA UD ROTI MUTIARA CIREBON - Agus Yudianto (BBM (Buletin Bisnis & Manajemen), 2016)
This research aims to develop a decision support system application on the system UD Roti Mutiara by applying the simplex method to determine the volume of production UD Roti Mutiara Cirebon. The criteria used to determine who is the source of power. As a condition to determine the volume of production.Determination of the amount of production for some products in a company, often a problem for the production manager. Activities that aim to maximize profit companies with limited resources that could be done by using the simplex method.This application is created using the Visual Basic programming language with support for Interbase DBMS. Results of this research is an application with a variable input gain of each product in production, resource requirements and the maximum available resources. Output from the application is the amount of product to be produced in order to obtain maximum benefit.Keywords : decision support system , specify the production , the simplex method.